Anxiety disorders among older adults: Empirically supported treatments and special considerations - Ishikawa, Rachel Zack; Vyas, Chirag; Okereke, Olivia (Clinical handbook of anxiety disorders: From theory to practice., 2020)
This chapter introduces the therapeutic approaches and major clinical themes in the treatment of late-life anxiety. Late-life anxiety disorders are prevalent, disabling, and often undertreated. Furthermore, when treatment is sought, most older adults are not offered empirically supported care, making effective treatment less likely. However, numerous modalities for effective treatment exist, including pharmacologic and non-pharmacologic approaches. Many older adults respond well to monotherapy strategies, while others benefit from augmented or combined approaches to address the needs most relevant to older adults. In this chapter, we review the evidence regarding appropriate psychopharmacologic and psychotherapeutic interventions for treating late-life anxiety disorders. We also address themes common to older adults, including cognitive impairment, age-related socioemotional changes, medical comorbidities, and treatment underutilization, and provide the reader with strategies for managing these complex issues in late-life anxiety. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Aging; Anxiety; Anxiety Disorders; Anxiety disorders; Late life anxiety; Older adults; Treatment